DAMPAK PERANG RUSIA-UKRAINA TERHADAP KETERSEDIAAN BBM (MINYAK BUMI) DI INDONESIA - Salsa Nabilla; Ghina Rahmi; Panji Dwi Prawira; Rinandita Wikansari (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2023)
The crude oil refining process supervised by the Indonesian government produces BBM (Fuel Oil). The increase in crude oil (BBM) prices caused by rising crude oil prices around the world as well as fluctuations in foreign exchange rates is a major problem. The complexity of the conflict between Russia and Ukraine is increasing, impacting energy prices and the world economy, including Indonesia. To respond to this, the government increased fuel subsidies. However, there are questions about how effective the policy will be. The impact of the Russia-Ukraine conflict on fuel availability in Indonesia is analyzed using a qualitative descriptive approach. Indonesia must consider the impact, even if it is not directly involved. Russian fuel imports increased significantly in 2021, but fell in 2022. In Russia, the conflict caused energy supply problems and fluctuations in energy prices around the world. Due to US threats against fuel imports from Russia, complexity increases, and Indonesia must choose between providing further subsidies or raising fuel prices to maintain stability. Although Indonesia's commodity exports increased, the conflict affected oil imports and crude oil prices, causing crude oil prices to rise domestically.